Early Ibadi Theology : Six kalam texts by 'Abd Allah b. Yazid al-Fazari - Faz, Abd Allah b. Yazid, active 767-775 (Islamic history and civilization ;, 2014)
Early Ibāḍī Theology offers the critical edition of six Arabic texts by the Ibāḍī scholar 'Abd Allāh b. Yazīd al-Fazārī (8th c.) recently discovered in Algeria that constitute the earliest extant body of kalām theology in Islam.